What style of leadership do women in STEMM fields perform? Findings from an international survey - Nash, M.; Davies, Amanda; Moore, R. (Public Library of Science, 2017)
It is widely acknowledged that women in science, technology, engineering, mathematics, and medicine (STEMM) fields are underrepresented in leadership globally. However, little is known about how leadership styles of women in STEMM relate to this underrepresentation. This article discusses findings from a survey examining how 61 women in STEMM define leadership and describe their own leadership styles. Using content analysis and drawing on Full Range Leadership Model factors, findings suggest that women define leadership and describe their own leadership styles using transformational factors. However, there was no consistency in how participants defined ideal leadership or how they defined their own leadership styles. This finding unsettles ideas of distinctly gendered leadership styles. We argue that expectations that leadership will be performed in distinctly gendered styles may be contributing to the underrepresentation of women in leadership roles in STEMM.